Transcatheter Repair and Replacement Technologies for Mitral Regurgitation: a European Perspective - Ooms, Joris F. (Curr Cardiol Rep, 2021)
PURPOSE OF REVIEW: We aimed to picture the contemporary landscape of available catheter-based repair and replacement solutions for mitral regurgitation (MR) in Europe. RECENT FINDINGS: Edge-to-edge repair remains the dominant technique for transcatheter mitral valve repair especially in the context of secondary mitral regurgitation. Two recent randomized trials reported seemingly contradicting clinical results with transcatheter edge-to-edge repair for patients with heart failure and severe secondary MR. A proportionality framework related to secondary MR was proposed to help explain inconsistencies but requires further research. (In)Direct annuloplasty primarily aims to correct secondary MR; however, the scientific basis seems less robust. One dedicated transcatheter heart valve has the CE mark for mitral valve replacement but requires transapical access. Balloon-expandable transcatheter aortic valve platforms are emerging for transvenous transseptal mitral replacement in the context of mitral annular calcification, a failing surgical mitral bioprosthesis, or annuloplasty. Advanced computed tomography imaging techniques improved pre-procedural planning and introduced the option for modeling and simulation. SUMMARY: Development of a toolbox of catheter-based technologies, complementary imaging modalities, and refined patient selection offer novel perspectives to high-risk patients with primary or secondary MR. Clinical trials are required to help formulate evidence-based guidelines for the management of mitral valve disease.